THE PRINCIPLES OF GOOD GOVERNANCE IN VILLAGE FUND ALLOCATION MANAGEMENT - Toni Nurhadianto; Fitri Agustina; Yaumil Khoiriah; Ulfah Tika Saputri (Proceeding International Conference on Information Technology and Business, 2019)
The objective of this research was to prove empirically the effect of the transparency principle, the accountability principles, and the participation principle on the village fund allocation management. The population of this research was the villages in Abung Kunang District. The sample of this research was 35 respondents taken from the village administrators who managed the village fund allocation, the head of the administration, and the head of the section. The data used in this research was the primary data. The data collecting technique used in this research was questionnaires. The data analysis technique used in this research was the multiple regression. The analytical tool used in this research was SPSS V.20 program. The results of this research showed that the transparency principle, the accountability principles, and the participation principle affected the the village fund allocation management.Keywords: Transparency, Accountability, Participation, Village Fund Allocation Management